TREND BLENDED LEARNING PADA PEMBELAJARAN DI NEW NORMAL DARI PANDEMI COVID-19 - Rita Hidayahwati (Bajang Institute, 2021)
The goal of this research is to explain the role of blended learning methodologies in the Covid-19 pandemic's